ТЕМПЫ РАЗВИТИЯ ПРОМЫШЛЕННОСТИ В КАЗАХСТАНЕ - Сансызбаева, Г. Н.; Кузенбаева, А. (Journal of Economic Research & Business Administration, 2015)
This article covers the dynamics of the industry, analyzing the key macroeconomic indicators. At present, Kazakhstan achieved financial stabilization, but at the same time, industrial production growth is unstable. The relative economic stability is associated primarily with the world price level and demand for major export commodities of the country. It should be noted, in most manufacturing industries remains the technical and technological backwardness.